COLLECTION OF POTATO VIRAL PATHOGENS, ITS VALIDATION AND MAINTENANCE - Yin, Zhimin; Michalak, Krystyna; Lebecka, Renata (Plant Breeding and Seed Science, 2017)
IHAR – PIB collection of potato viral pathogens has been maintained since 1970s. Currently there are 258 isolates in the collection representing 12 potato viruses, named PVY, PVM, PVS, PLRV, PVA, PVX, PAMV, BMYV, TBRV, AMV, CMV and TRV. The viruses are maintained in potato plants in vivo in the greenhouse (246 isolates), in potato plantlets cultured in vitro (12 isolates), in frozen leaves (two copies each of the 246 isolates) and in freeze-dried tissue (234 isolates).